Differences between structural and functional environmental heterogeneity caused by seed dispersal (Functional Ecology, 2004)
* 1This paper explores the idea that functional heterogeneity (variability of a system property affecting ecological processes) is only a fraction of the available structural heterogeneity (variability of a property measured without reference to ecological effects) caused by non-random propagule dispersal. We report the effect of acorn dispersal by jays on the light environment experienced by Holm Oaks (Quercus ilex L.) during early recruitment in a Mediterranean montane forest. * 2Four light variables were estimated by studying hemispherical photographs: direct site factor (DSF); indirect site factor (ISF); and potential direct radiation during April (PDRApril) and August (PDRAugust). Means and variances of these variables were compared before and after the dispersal of acorns by jays. * 3The landscape occupied by Holm Oaks was very heterogeneous, which translated into differences in the available light among microhabitats of up to one order of magnitude. * 4Because of the spatial pattern of acorn dispersal, the light environment of the oaks during their establishment was much more homogeneous than that in the whole landscape. * 5This demonstrates that the heterogeneity relevant for plant recruitment is not necessarily that of the landscape as a whole.